2008
DOI: 10.1111/j.1439-0531.2008.01178.x
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Regulation of Foetal Development in Nuclear Transfer Animal Models

Abstract: Somatic cell nuclear transfer (SCNT, 'cloning') holds great potential for agricultural applications, generation of medical model animals, transgenic farm animals or by 'therapeutic cloning' for generating human embryonic stem cells for the treatment of human diseases. However, the low survival rate of SCNT-derived pregnancies represents a serious limitation of the current technology. In order to overcome this hurdle, a deeper understanding of the epigenetic reprogramming of the somatic cell nuclei and its effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 87 publications
(103 reference statements)
0
15
0
Order By: Relevance
“…Many studies have examined cloned mouse and bovine embryos and identified epigenetic alterations in X chromosome inactivation and imprinting. Differences in DNA methylation both in general and of specific genes and repeat sequences have been reported [35]. One previous study observed similar demethylation activity in cloned and control pig embryos with respect to two repetitive sequences: a centromeric satellite and the PRE1 short interspersed element (SINE) [36].…”
Section: Discussionmentioning
confidence: 81%
“…Many studies have examined cloned mouse and bovine embryos and identified epigenetic alterations in X chromosome inactivation and imprinting. Differences in DNA methylation both in general and of specific genes and repeat sequences have been reported [35]. One previous study observed similar demethylation activity in cloned and control pig embryos with respect to two repetitive sequences: a centromeric satellite and the PRE1 short interspersed element (SINE) [36].…”
Section: Discussionmentioning
confidence: 81%
“…It comes as no surprise that epigenetic modification of the genome is disrupted in nuclear transfer embryos; this phenomenon has been extensively reviewed elsewhere (3,18,51,84). It is somewhat surprising, however, that genes involved in epigenetic processes were overwhelmingly downregulated in embryos derived from SCNT.…”
Section: Discussionmentioning
confidence: 99%
“…Interest has dramatically increased as it has become clear that epigenetics will be essential to understanding many topical biological phenomena such as stem cells [14], nuclear transfer (cloning) [15], cellular reprogramming [16], aging [17], evolution and speciation [18], and agriculture [19].…”
Section: Relevance Of Epigenetics To Modern Medicinementioning
confidence: 99%